Images-Allegories in the Medieval Sculpture of Armenia and the South Caucasus - Hakobyan, Zaruhi A. (Actual Problems of Theory and History of Art, 2023)
The article deals with the sculptural faces, or heads, which are very popular in the art of medieval Armenia and the South Caucasus. They often occupy the outer niches of the churches, decorate altar parts, or eastern facades. These generalized images, devoid of individual features, differ markedly from the donator and other images. The iconographic analysis and comparisons with similar images from early Christian art (floor mosaic, textile, sculpture) give every reason to consider them as images-allegories, or personifications symbolizing natural elements and other symbolic images. For a better understanding of the meaning of these sculptural heads, or faces, the article focuses on the decorative program of two churches — Syuni-Vank (7th-century Armenia) and Kumurdo (10th-century Georgia), which coincide in the composition and groups of images.The research was done within the framework of a grant for the project: “Sculpture Decoration of Ruined and Less Studied Church Complexes of the 12th–14th centuries in Armenia” (21T-6E291), provided by the Science Committee of the Ministry of Education, Science, Culture and Sports of RA.
Keywords: Syuni-Vank; Sisavan; sculpture; head; bust; image; allegory; Kumurdo; Aghtamar; Tatev